The Accuracy of Brachial Artery Volume Flow as a Predictor of Brachiocephalic Arteriovenous Fistula Maturation - Patrianef Darwis (Journal of Global Pharma Technology, 2020)
Objective: This study aims to investigate brachial artery volume flow accuracy in predicting AVF maturity. Methods: This was a cross-sectional study involving 80 patients that underwent AVF creation in Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Parameters recorded include demographic data, ultrasound parameters in six weeks after AVF creation, and complications. Diagnosis tests were performed to determine the area under the curve (AUC), cut-off, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Results: Of 80 patients that underwent brachiocephalic AVF, we found that 64 (80%) successfully mature, and 16 (20%) failed to mature. Receiver operating characteristic (ROC) for brachial artery volume flow in predicting brachiocephalic AVF had AUC of 97,6 %. With cut-off brachial artery volume flow of 700 ml/minute, the sensitivity, specificity, PPV, NPV, and accuracy were 98.44 % (95 % CI 91.6-99.7%), 87.5 % (95 % CI 63,9 % - 96.5 %), PPV 96.9 % (95% CI 89.4-99.15%) NPV 84.6 % (95 % CI 66.5 % - 93.8 %) 93.33 % (95 % CI 70.1-98.8%), respectively. Conclusions: Brachial artery volume flow six weeks after AVF creation is an accurate parameter in predicting brachiocephalic AVF maturity. Keywords: brachial artery volume flow, maturity, arteriovenous fistula